2008
DOI: 10.1086/524709
|View full text |Cite
|
Sign up to set email alerts
|

A Deletion in the Chemokine Receptor 5(CCR5)Gene Is Associated with Tickborne Encephalitis

Abstract: Tickborne encephalitis (TBE) virus infections can be asymptomatic or cause moderate to severe injuries of the central nervous system. Why some individuals develop severe disease is unknown, but a role for host genetic factors has been suggested. To investigate whether chemokine receptor CCR5 is associated with TBE, CCR5Delta32 genotyping was performed among Lithuanian patients with TBE (n=129) or with aseptic meningoencephalitis (n=76) as well as among control subjects (n=134). We found individuals homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(144 citation statements)
references
References 14 publications
6
134
1
3
Order By: Relevance
“…Those individuals who were CCR5Δ32 homozygous had a higher frequency of multisystemic symptoms such as lymphadenopathy, neurological deficits and gastrointestinal complications. Similar results were obtained for TBEV in which individuals possessing the CCR5Δ32 allele were found to have a statistically higher frequency of symptomatic TBEV infection than subjects who were homozygous for WT CCR5 [68].…”
Section: Host Determinants Of Flavivirus Encephalitissupporting
confidence: 77%
“…Those individuals who were CCR5Δ32 homozygous had a higher frequency of multisystemic symptoms such as lymphadenopathy, neurological deficits and gastrointestinal complications. Similar results were obtained for TBEV in which individuals possessing the CCR5Δ32 allele were found to have a statistically higher frequency of symptomatic TBEV infection than subjects who were homozygous for WT CCR5 [68].…”
Section: Host Determinants Of Flavivirus Encephalitissupporting
confidence: 77%
“…Results from previous cohort studies revealed a direct correlation between CCR5 Δ32 homozygosity and symptomatic disease during infections with WNV and TBEV [257,258]. However, the results from recent follow-up studies using larger cohorts failed to show any association between CCR5 deficiency and symptomatic infection with WNV or TBEV [259].…”
Section: Susceptibility Factors For Arboviral Encephalitis: Lessons Fmentioning
confidence: 88%
“…Given the similarities in the pathogenesis of WNV and TBEV, Kindberg et al [105] evaluated the role of CCR5 in the context of TBEV infection in humans. Their study evaluated a cohort of Lithuanian patients infected with TBEV and demonstrated an increase in CCR5D32 allele frequency as well as homozygous frequency among TBEV patients with encephalitis compared with TBEV-negative meningoencephalitis cases or healthy age-, ethnicity-and geographically matched controls.…”
Section: Ccr5mentioning
confidence: 99%